Effects of saturated versus unsaturated fatty acids on metabolism, gliosis, and hypothalamic leptin sensitivity in male mice. (1st February 2023) - Fernández-Felipe, Jesús; Valencia-Avezuela, Maria; Merino, Beatriz; Somoza, Beatriz; Cano, Victoria; Sanz-Martos, Ana B.; Frago, Laura M.; Fernández-Alfonso, Maria S.; Ruiz-Gayo, Mariano; Chowen, Julie A.
ABSTRACT: Background: Development of obesity and its comorbidities is not only the result of excess energy intake, but also of dietary composition. Understanding how hypothalamic metabolic circuits interpret nutritional signals is fundamental to advance towards effective dietary interventions. Objective: We aimed to determine the metabolic response to diets enriched in specific fatty acids. Methods: Male mice received a diet enriched in unsaturated fatty acids (UOLF) or saturated fatty acids (SOLF) for 8 weeks. Results: UOLF and SOLF mice gained more weight and adiposity, but with no difference between these two groups. Circulating leptin levels increased on both fatty acid-enriched diet, but were higher in UOLF mice, as were leptin mRNA levels in visceral adipose tissue. In contrast, serum non-esterified fatty acid levels only rose in SOLF mice. Hypothalamic mRNA levels of NPY decreased and of POMC increased in both UOLF and SOLF mice, but only SOLF mice showed signs of hypothalamic astrogliosis and affectation of central fatty acid metabolism. Exogenous leptin activated STAT3 in the hypothalamus of all groups, but the activation of AKT and mTOR and the decrease in AMPK activation in observed in controls and UOLF mice was not found in SOLF mice. Conclusions: Diets rich in fatty acids increase body weight and adiposity even if energy intake is not increased, while increased intake of saturated and unsaturated fatty acids differentially modify metabolic parameters that could underlie more long-term comorbidities. Thus, more understanding of how specific nutrients affect metabolism, weight gain, and obesity associated complications is necessary.